Government Capacity Gap in Handling Covid-19 in Lampung Province - Robi Cahyadi Kurniawan; Dodi Faedlulloh; Arizka Warganegara; Dedy Hermawan (Universitas Muhammadiyah Tangerang, 2022)
As a transit area for economic activities between the islands of Sumatra and Java, Lampung Province has a high risk of becoming a point of virus transmission. Local governments must be able to deal with Covid-19. This study aims to assess the capacity of the Lampung Provincial Government in dealing with Covid-19. Government capacity is essential for crisis management, such as during a pandemic. The research approach used is a qualitative method that includes primary and secondary data and focuses on reviewing literature from reliable sources. The findings reveal that the capacity of the Lampung Provincial Government in terms of fiscal capacity, infrastructure, operational capacity, and political capacity is still lacking. The implication is that the Lampung Provincial Government needs to evaluate and prioritize capacity building, especially political capacity in terms of responsive political communication to maintain public trust. Provinsi Lampung sebagai wilayah transit kegiatan ekonomi antara pulau Sumatera dan Jawa berisiko tinggi menjadi titik penularan virus. Pemerintah daerah harus mampu menangani Covid-19. Kajian ini bertujuan untuk menilai kapasitas Pemerintah Provinsi Lampung dalam menangani Covid-19. Kapasitas pemerintah merupakan aspek penting untuk manajemen krisis seperti saat pandemi. Pendekatan penelitian yang digunakan adalah metode kualitatif yang mencakup data primer dan data sekunder dan difokuskan pada tinjauan pustaka dari sumber yang dapat dipercaya. Hasil temuan mengungkapkan bahwa kapasitas Pemprov Lampung dalam hal kapasitas fiskal, kapasitas infrastruktur dan operasional, serta kapasitas politik masih kurang. Implikasinya, Pemerintah Provinisi Lampung perlu melakukan evaluasi dan melakukan prioritas pengembangan kapasitas, khususnya kapasitas politik dalam hal komunikasi politik yang responsif untuk menjaga kepercayaan publik.